Storytelling and Cybercartography: The William Commanda story - Thumbadoo, R.V. (Romola Vasantha); Taylor, D.R. (Fraser) (2019)
This chapter examines the storytelling approach to relationship building and knowledge generation in the work of the late Indigenous Elder William Commanda (1913–2011), as re-vitalized in Cybercartography. Storytelling is central to Cybercartography and is creating new ground for the presentation and performance of an increasing number of narratives which are reconceptualizing time and space. Digital technologies are magnifying outreach. William Commanda was born at the beginning of the last century, on the eve of the First World War, on the first reserve created in Canada. He is the longest known guardian of the ancient sacred mnemonic Wampum oral storytelling and animative record keeping heritage of his ‘Mamiwinini/Nomad’ Algonquin ancestors. He was born of oral tradition, raised in the generic prototype of Algonquian linguistics, and spoke multiple dialects. He also learned to speak and write in French and English, and storytelling was his forte. He created a global eco-peace community, the Circle of All Nations. He relied heavily on oral storytelling, talking circles and other semiotic and semantic mechanisms to advance cross-cultural understanding, bridge-building, informa